Superconducting undulator activities at the European X-ray Free-Electron Laser Facility - Casalbuoni, Sara; Abeghyan, Suren; Alanakyan, Levon; Baader, Johann; Barbanotti, Serena; Decking, Winfried; Felice, Massimiliano Di; Eckoldt, Hans-Jörg; Englisch, Uwe; Geloni, Gianluca; Grattoni, Vanessa; Grau, Andreas; et al. (Frontiers in Physics, 2023)
Since more than five years superconducting undulators (SCUs) are successfully delivering x-rays in storage rings. European XFEL plans to demonstrate the operation of SCUs in X-ray FELs. For the same geometry, SCUs can reach higher peak field on axis with respect to all other available technologies, offering a larger photon energy tunability range. The application of short period SCUs in a high electron beam energy FEL > 11 GeV will enable lasing at very hard X-rays > 40 keV. The large SCUs tunability range will allow to cover the complete photon energy range of the soft X-ray experiments at European XFEL, without changing electron beam energy, as currently needed with the installed permanent mangnet undulators. For a possible CW upgrade under discussion at European XFEL with a lower electron beam energy of about 7-8 GeV, SCUs can provide the same photon energy range as available at present with the permanent magnet undulators and electron energies. This paper will describe the potential of SCUs for X-ray FELs. In particular, it will focus on the different activities ongoing at European XFEL and in collaboration with DESY to allow the implementation of SCUs in the European XFEL in the next years.